Some Fiscal Calculus - Uhlig, Harald (American Economic Review, 2010)
The 2008 financial crisis and its policy response has urgently raised the old question of the impact of fiscal policy, in particular government spending and tax cuts, on the economy. This paper contributes to this debate, using a simple neoclassical growth model with endogenous labor, adding fiscal instruments to provide a positive rather than normative analysis of the impact of fiscal policy shocks. It is shown that the timing of the tax response to the ensuing deficits may be crucial and that the calculations of fiscal multipliers can be misleading. Keywords: JEL codes: 2 1 A short introduction What is the impact of fiscal policy on the economy? How large are the “multipliers ” of government spending and tax cuts? This old question has recently received considerable attention. This paper contributes to answering that question by thinking through fiscal multipliers in a baseline neoclassical